THE HISTORICAL SITE UMPAK RESHOGATI IN SOGATEN (A STUDY OF CULTURAL VALUES AND THEIR POTENTIALS FOR RESOURCES OF HISTORY EDUCATION FOR HIGH SCHOOL XI GRADERS) - Stanislaus Aris Wahyuwitomo; Satrijo Budiwibowo; Moh Rifa’i (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
IT advances has been penetrating all of life including education. Educators need to help students exposed to cultural values to enable them filter things bad along with the IT invasion. Historical sites along with cultural values could be beneficial for such educational purposes. This research aims at investigating the historical site Umpak Reshogati located in Sogaten, Manguharjo District, Madiun City as well as the surrounding cultural values as potentials for educational sources of history education. This study involved such informants as the caretaker of the site, local citizens, local leaders, and government officials. Observation was carried out for 6 months beginning September 2019. Findings indicate that the historical site Umpak Reshogati was once the hall of Purabaya Regency, local people holds in high esteem such cultural values as gotong-royong (solidarity), faithfulness, and tolerance which are potentials for resources of history education.